Radiation toxicity in prostate cancer patients - Stanić, Jelena; Stankovic, Vesna; Nikitovic, Marina (Medicinski podmladak, 2021)
AbstractProstate cancer (PC) is the most frequent male tumor, accounting for about one-third of all cancers in men. Because survival is often favorable regardless of therapy, treatment decisions may depend on therapy-specific health outcomes. The majority of men initially diagnosed with localized PC ultimately die with, rather than of, their disease. As a result, men who are diagnosed will live many years with the treatment's sequelae.The major therapeutic strategies include radical prostatectomy or external beam radiotherapy. Radiotherapy is one of the curative treatment options. The tumor dose-response relationship has been studied and is widely accepted. The unsatisfactory local control with doses
Keywords: prostate cancer; radiotherapy; radiation toxicity